Bioassay-guided isolation and identification of antimicrobial and cytotoxic compounds from the leaves of Muntingia calabura / Adila Sahida Sufian - Sufian, Adila Sahida (2013)
In the present work, isolation and identification of antimicrobial and cytotoxic compounds from the leaves of Muntingia calabura (Elaeocarpacea) was carried out based on bioassay-guided approach. The methanol leaf extract of M. calabura (MCME) and its partitioned extracts [petroleum ether (MCPE), ethyl acetate (MCEA) and aqueous (MCAQ)] were subjected to antimicrobial and cytotoxic activities using micro-broth dilution and MTT assays, respectively. MCEA, which appeared to be the most active extract against MSS A (S. aureus 25923) (MIC - 125 μg/mL) and HL60 cell line (human acute promyelocytic leukemia) (IC50 = 17.26 μg/mL), was further fractionated using vacuum liquid chromatography (VLC) to afford seven fractions (F1-F7).